Hemodynamics During Development and Postnatal Life - Gregorovicova, Martina; Lashkarinia, S Samaneh; Yap, Choon Hwai; Tomek, Viktor; Sedmera, David (Advances in experimental medicine and biology, 2024)
A well-developed heart is essential for embryonic survival. There are constant interactions between cardiac tissue motion and blood flow, which determine the heart shape itself. Hemodynamic forces are a powerful stimulus for cardiac growth and differentiation. Therefore, it is particularly interesting to investigate how the blood flows through the heart and how hemodynamics is linked to a particular species and its development, including human. The appropriate patterns and magnitude of hemodynamic stresses are necessary for the proper formation of cardiac structures, and hemodynamic perturbations have been found to cause malformations via identifiable mechanobiological molecular pathways. There are significant differences in cardiac hemodynamics among vertebrate species, which go hand in hand with the presence of specific anatomical structures. However, strong similarities during development suggest a common pattern for cardiac hemodynamics in human adults. In the human fetal heart, hemodynamic abnormalities during gestation are known to progress to congenital heart malformations by birth. In this chapter, we discuss the current state of the knowledge of the prenatal cardiac hemodynamics, as discovered through small and large animal models, as well as from clinical investigations, with parallels gathered from the poikilotherm vertebrates that emulate some hemodynamically significant human congenital heart diseases.
Keywords: Heart; Heart Defects, Congenital; vrozené srdeční vady; zvířata; Humans; Hemodynamics; hemodynamika; srdce; lidé; Animals